Redupnya Cahaya Tuan Guru: Dekharismatisasi Sosok Tuan Guru Terlibat Dalam Politik - Wahyu Trisno Aji; Fauzul Kabir (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
This article aims to explain how Tuan Guru is Decharismatized when involved in politics. In the Sasak tribe on the island of Lombok, West Nusa Tenggara (NTB) province, the figure of Tuan Guru is seen as a religious figure or cleric whose main purpose of existence is none other than to continue the baton of preaching from the Prophet Muhammad SAW. The figure of Tuan Guru in Lombok is none other than an important figure who guides society more specifically in the order of life according to religious teachings. However, the view of the Lombok community towards Tuan Guru with charisma gradually faded when Tuan Guru was involved in the world of politics, namely a world where uncertainty and power are the main heart. From the results of Agus Dedy Putrawan's research (2014) that the Sasak community sees that when Tuan Guru is involved in politics, it has the potential to move away from the main role as a preacher, then many other factors cause the figure of Tuan Guru to experience Decharismatization when this religious figure is involved in politics.